PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS SISTEM PENGAMBILAN KEPUTUSAN SELEKSI CALON APARAT DESA - Engge, Indriani Wehelmina; Gabriel, Cecilia Dai Payon Binti; Adis, Alexander (JUTECH : Journal Education and Technology, 2024)
The research on the decision-making system for selecting prospective village officials at the Ndara Mane village office using the AHP method has yielded valuable results. Currently, the village head still relies on manual methods for screening prospective officials, which involves reviewing documents like applications and resumes. Unfortunately, there is evidence of fraud in the selection process, with priority given to individuals who have personal relationships with existing village officials or the village head. A decision-making system is crucial in effectively and efficiently resolving problems by selecting alternative actions. The AHP method, which evaluates and makes decisions based on multiple criteria, can help facilitate and resolve complex issues in the selection process. Additionally, a personnel management information system has been implemented in BKPSDM Southwest Sumba Regency to integrate employee data, such as education, rank, and class information. This system plays a vital role in viewing, adding, changing, and deleting employee data. The purpose of this research is to effectively utilize the decision-making system and personnel management information system to improve the selection process of prospective officials.